The Influence of Influencer Marketing, Content Marketing, and Electric Word of Mouth (E-Wom) in Tiktok Application in Purchasing Decision of Scarlett Whitening of Students at Universitas Pelita Harapan Medan - Cherish Calim; Clerent Cheong; Devina Gunawan; Joshe; Stefani Sunasli (MultiTech Publisher, 2020)
This study investigates the impact of influencer marketing, content marketing, and Electric Word of Mouth (E-WOM) on the purchasing decisions of Scarlett Whitening products among students at Universitas Pelita Harapan Medan through the TikTok application. Leveraging a mixed-methods approach comprising surveys and in-depth interviews, this research uncovers the complex relationship between these marketing strategies and student consumer behavior. Preliminary findings suggest that influencer marketing and compelling content hold substantial sway over purchasing decisions, with E-WOM serving as both an amplifying force for brand trust and a potential source of negative influences. These insights provide valuable guidance for marketers seeking to engage effectively with the student demographic in the unique context of TikTok marketing at Universitas Pelita Harapan Medan